Association of pulse pressure and aortic root diameter in elderly Chinese patients with chronic heart failure - Chen, Lu; Xie, Wenhui; Hong, Xuhui; Hong, Huashan (Frontiers in Cardiovascular Medicine, 2024)
Abstract Background: High pulse pressure (PP) and aortic root diameter (AoD) are hallmarks of arterial stiffness or vascular aging and they are considered as risk factors for age-related cardiovascular disease, including heart failure (HF). However, the relationship between PP and AoD in patients with heart failure (HF) is uncertain. This study aimed to evaluate the relationship between PP and AoD in the middle-aged and the elderly with HF. Methods: A total of 1027 Chinese middle-aged and elderly patients with HF, including HF with reduced ejection fraction (HFrEF), HF with mid-range EF (HFmrEF), and HF with preserved EF (HFpEF) were included in this study. Pearson correlation analysis was used to evaluate the relationship between PP and AoD in the three types of HF. Multiple linear regression analysis was performed to assess the factors that affected AoD. Multivariate logistic regression was performed to determine the association between the PP level quartiles and AoD. The results were validated in an independent dataset included a total of 378 consecutive patients with HFrEF hospitalized at the Pingtan Branch of Fujian Medical University Union Hospital (Fujian, China). Results: There was a positive correlation between PP and AoD in the middle-aged and the elderly with HFrEF. Multiple linear regression analysis revealed that PP, age, and body mass index (BMI) were independently correlated with AoD in HFrEF patients. In multivariate logistic regression analysis, an increased risk of aortic root dilation was observed in the highest quartile of the PP level compared with the lowest quartile. Age significantly interacted with PP (p = 0.047). A significant association between PP levels and AoD was only observed in patients ≥ 65 years old, but not in patients < 65 years old. In the validation dataset, PP was independently related to AoD in patients with HFrEF (β = 0.205, p = 0.001). Conclusions: PP level was independently and positively associated with AoD, especially in the elderly with HFrEF, but not in patients with HFmrEF and HFpEF. Arterial stiffening or vascular aging may play a certain role in the elderly HFrEF patients. Keywords: pulse pressure, aortic root diameter, heart failure, arterial stiffness